Molecular phylogeny of cycads inferred from rbcL sequences - Treutlein, Jens; Wink, Michael (The Science of nature, 2002)
. The chloroplast gene rbcL was sequenced to elucidate the evolution of the gymnosperm plant order Cycadales. In accordance with traditional systematics, the order Cycadales and the corresponding genera cluster as monophyletic clades. Among them, the genus Cycas forms a basal group. The genetic distances within the genus Encephalartos and between the sister groups Encephalartos, Lepidozamia and Macrozamia, are unexpectedly small, suggesting that the extant species are the result of Miocene and Pliocene speciation. Their distribution in Africa or Australia, respectively, may therefore rather be due to long-distance dispersal than to Cretaceous continental drift, as had previously been assumed. The rbcL sequences also indicate that the colonisation of Madagascar by Cycasthouarsii occurred only recently as the sequences of C.thouarsii and Cycasrumphii from Indonesia are identical. In contrast, the divergence of the Cycadaceae and Zamiaceae apparently occurred in the Mesozoic.